2017
DOI: 10.1371/journal.pone.0171346
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring gait in multiple sclerosis with novel wearable motion sensors

Abstract: BackgroundMobility impairment is common in people with multiple sclerosis (PwMS) and there is a need to assess mobility in remote settings. Here, we apply a novel wireless, skin-mounted, and conformal inertial sensor (BioStampRC, MC10 Inc.) to examine gait characteristics of PwMS under controlled conditions. We determine the accuracy and precision of BioStampRC in measuring gait kinematics by comparing to contemporary research-grade measurement devices.MethodsA total of 45 PwMS, who presented with diverse walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 49 publications
(77 reference statements)
9
67
0
Order By: Relevance
“…Other systems commonly detect gait by placing sensors at the lumbar [2527] or shank [8,27,28] of the subject. Many of these systems are shown to be reasonably accurate [29,30] and repeatable (ICC ranging between 0.75 and 0.90) [31].…”
Section: Discussionmentioning
confidence: 99%
“…Other systems commonly detect gait by placing sensors at the lumbar [2527] or shank [8,27,28] of the subject. Many of these systems are shown to be reasonably accurate [29,30] and repeatable (ICC ranging between 0.75 and 0.90) [31].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier generations (BioStamp RC TM and investigational prototypes) of the technology have been used in academic research, including motor assessments in Parkinson disease [28], gait assessment in multiple sclerosis [13], posture classification in Huntington disease [12], postural sway in multiple sclerosis [29], and periodic leg movements in sleep (unpublished data). Additional independent research with BioStamp technology has looked at ambulatory vectorcardiography [30], spasticity [31], and more granular activities of daily living (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Often their form factor, size, and wear locations impede continuous wear, interfere with daily activities, make them conspicuous, and compromise sleep. Recent studies have shown that lightweight, conformal sensors provide an alternative in studies focused on Huntington disease [12], multiple sclerosis [13], physical rehabilitation [14], and cardiac monitoring [15]. Here, we present a validation study conducted with a novel wireless remote monitoring system (BioStamp nPoint®; MC10 Inc., Lexington, MA, USA) that includes lightweight, conformal, multimodal biosensors to capture continuous physiological data in simulated home and clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Two of these devices were the BioStamp RC and the MTx inertial sensor. The research demonstrated remarkably low measurement errors (i.e., high accuracy) for capturing actual steps taken compared with estimates from an ActiGraph GT3X during a 6-minute walk on a motorized treadmill in persons with MS (i.e., 0.8% and 0.9%, respectively, vs. 10.1%) [79]. One potential explanation for the superiority of the BioStampRC and MTx relative to the GT3X might involve the positioning of the BioStampRC and MTx inertial sensor on the shanks of the leg, as this allows for assessment of temporal gait paramenters such as stride time, swing time, and step time.…”
Section: Research From 2013–2017: What Is New?mentioning
confidence: 99%